A new species of Lysmata Risso, 1816 (Crustacea, Decapoda, Lysmatidae) from the Gulf of Mexico - Prakash, Sanjeevi; Baeza, J. Antonio (Zootaxa, 2017)
A new species of peppermint shrimp, Lysmata baueri n. sp., is described based on a single specimen from the eastern Gulf of Mexico. The new species can be distinguished from other morphologically similar species of Lysmata Risso, 1816 by the number of teeth, length and shape of the rostrum, the length of the antennular peduncle relative to the scaphocerite, the number of meral and ischial articles in the second pereiopods, and the number of spines on the flexor margin of the dactyli from the third to fifth pereiopods. Morphological characters demonstrate that L. baueri n. sp., is most closely related to the eastern Pacific L. californica (Stimpson, 1866), L. nayaritensis Wicksten, 2000 and L. porteri (Rathbun, 1907).